Moving From Indifference to Responsibility: Reframing Environmental Behavior Among College Students in Israel - Dopelt, Keren; Loren, Ori; Gapich, Gal; Davidovitch, Nadav (Frontiers in Climate, 2021)
Objectives: To examine the level of knowledge, attitudes, and behavior of students on topics related to climate change and the relationship between those variables. Methods: A cross-sectional study using an online questionnaire, including 704 students. Statistical analysis was performed using Pearson correlations, t-tests, one-way ANOVA, and regression models. Results: Only 42% of participants understood what climate change meant, and 14% indicated their indifference toward it. Students had a moderate level of knowledge about the impact of climate change, and their attitudes were moderately positive, yet they demonstrated poor environmental behavior. We found positive relationships between variables, with attitudes mediating the relationship between knowledge and behavior. Women demonstrated more pro-environmental behavior than men. Conclusions: Our results highlight the importance of raising awareness of climate change's effects and its mitigation. Pro-environmental behavior requires long-term thinking and priorities for the future rather than benefits in the present. Future environmental education campaigns should emphasize individual contributions to environmental impacts in the context of climate change, as well as environmentally relevant consumption habits. We suggest including an introductory reflective and emancipatory course in environmental studies in all departments, emphasizing public health aspects.